Warrick score in rheumatoid-arthritis interstitial lung disease: a promising tool for assessing the extent and progression of lung involvement - Duygu Temiz Karadag; Sevtap Dogan; Neslihan Gokcen; Oznur Sadioglu Cagdas; Ayten Yazici; Ayse Cefle (Advances in Rheumatology)
Abstract Background The clinical manifestations and course of rheumatoid arthritis-associated interstitial lung disease (RA-ILD) exhibits considerable heterogeneity. In this study, we aimed to explore radiographic progression over a defined period, employing the Warrick score as a semi-quantitative measure in early RA-ILD, and to assess the associated risk factors for progression. Methods RA-ILD patients underwent consecutive Warrick scoring based on initial high-resolution computed tomography (HRCT) at diagnosis and the first follow-up. Associations between Warrick scores, pulmonary function tests, and patient characteristics were analyzed. The ROC curve assessed the predictive performance of the Warrick score change rate for ILD progression, while multivariable logistic regression analysis identified risk factors for progression. Results Significant correlations were found between Warrick scores and age at RA-ILD diagnosis, age at ILD diagnosis, and baseline DAS28-ESR. For the severity score, correlations were r = 0.359, r = 0.372, and r = 0.298 (p = 0.001, p < 0.001, p = 0.014, respectively); for the extent score, r = 0.364, r = 0.318, and r = 0.255 (p = 0.001, p = 0.005, p = 0.038, respectively); and for the total score, r = 0.376, r = 0.367, and r = 0.280 (p < 0.001, p = 0.001, p = 0.022, respectively). Annual changes in severity, extent, and total Warrick scores showed sensitivities of 91–97% and specificities of 98% for predicting progression over a 5-year follow-up. Cut-off values were 0.0278 for the severity score (AUC 0.954), 0.0227 for extent score (AUC 0.976), and 0.0694 for total score (AUC 0.946). Warrick severity, extent, and total scores increased significantly during follow-up. Age > 50 years (OR 7.7; p = 0.028) and baseline usual interstitial pneumonia (UIP) pattern (OR 3.1, p = 0.041) were identified as risk factors for progression. Conclusions Advanced age and UIP pattern were significant risk factors for progression. Warrick scoring may may help predict progression in RA-ILD, particularly through changes in severity, extent, and total scores. Due to the retrospective design and small sample size, further prospective studies with larger cohorts are needed to confirm these findings and validate Warrick scoring as a reliable marker for RA-ILD progression.